ANALISIS KEPUTUSAN BERMIGRASI TENAGA KERJA ASAL KABUPATEN OGAN ILIR KE MALAYSIA - MARYADI, RENI NURLINA (I-Economics, 2016)
Ogan Ilir (OI) is one of the most labor sending migrants from other areas in South Sumatra. Based on data from employment abroad Ogan Ilir in 2011 until 2015 are more likely to state Malaysia. The persistently high unemployment rate can not be offset by the availability of existing employment. That many residents of Ogan Ilir must decide to migrate to work outside the region and even overseas as migrant workers in countries such as Malaysia. The low level of wages and employment in Ogan Ilir is a driver of labor migration. While the economic circumstances are relatively better, more open employment opportunities, income levels are high is that there are pull factors in destination countries.This study aims to analyzing the factors that affect decision to migrate labor Indonesian of Ogan Ilir’s migrated to Malaysia. The design of research cross tabulation with using data BP3TKI in 2015, this research uses primary data from 138 respondents to the migrate and do not migrate to Malaysia but ever follow PAP program debriefing end of departure. Estimation of decision to migrate is analyzed uses Binary Logistic Regression Model and test Chi Square Hosmer and Lemeshow with significance level of 0.05. The study states that the factors that influence the decision to migrate isage, the marital status, the load amenability of family, the ownership of land, the migration networkand the remittances.Keywords: Ogan Ilir’s (OI), Indonesian workers, Decision to migrate, Decisions not migrate,Logistic Regression Model